Barokowe „wojny” (z) ciałem - Krawiec-Złotkowska, Krystyna (Collectanea Philologica, 2024)
The article presents the topic of the allegorical war against the body, which in the post-Tridentine culture was perceived in an ambivalent way: as sinful and evil and as good because it was the work of God. Allegorical battles were also presented, in which the body is a tool in battle. Attention was paid to the sources of this ambivalence – the dualistic nature of man. The different needs of the soul and body have the nature of a conflict. The fight for man is fought by: Amor Divinus and Amor profanus. The bodies of people who lived piously and wanted to achieve mystical union with Christ are shown in the laudatory theme – similarly to. The bodies of sinners who succumbed to sensual temptations during their lives are depreciated, despised, presented in turpistic aesthetics, and ultimately condemned to the torments of hell. The ancient sources of this type of imagery were indicated – the ideas of Plato, the thought of Seneca and Horace – and the affiliations between ancient culture and post-Tridentine poetry. It has been established that the Body of Christ has a unique status. Descriptions of the tormented Jesus, permeated with brutal naturalism, were intended to provoke reflection and influence the conversion of sinners. The Judeo-Christian tradition and the heritage of Greco-Roman antiquity were transformed and adapted to the post-Tridentine culture in the 17th century.